A DEA model for efficiency evaluation with undesirable output: an application of paper mills along Huai River. (3rd January 2012) - Wu, Jie; Yan, Hong; Zhou, Zhixiang; Liang, Liang
This paper focuses on evaluating the operations efficiency of paper mills located on the banks of Huai River in China using data envelopment analysis (DEA). We divide the outputs as desirable (good) and undesirable (bad) outputs and consider them simultaneously. In this manner, we expect to identify the environmental characteristics of efficiency evaluation problem with undesirable outputs. Different from conventional DEA models, a novel model is constructed in this paper to evaluate the performance of decision-making units (DMUs) from both sides of desirable and undesirable outputs. Based on the proposed model, some managerial suggestions for the poorly performing DMUs to improve their efficiency are given. Finally, a practical application on the efficiency evaluation on 31 paper mills is conducted to illustrate the proposed model.